Intelligent computing systems : first International Symposium, ISICS 2016, Mérida, México, March 16-18, 2016, Proceedings /: first International Symposium, ISICS 2016, Mérida, México, March 16-18, 2016, Proceedings. (2016) - Unknown
No abstract available